siRNA therapy in osteoarthritis: targeting cellular pathways for advanced treatment approaches - Li, Yunshen; Zhao, Jianan; Guo, Shicheng; He, Dongyi (Frontiers in Immunology, 2024)
Osteoarthritis (OA) is a common joint disorder characterized by the degeneration of cartilage and inflammation, affecting millions worldwide. The disease's complex pathogenesis involves various cell types, such as chondrocytes, synovial cells, osteoblasts, and immune cells, contributing to the intricate interplay of factors leading to tissue degradation and pain. RNA interference (RNAi) therapy, particularly through the use of small interfering RNA (siRNA), emerges as a promising avenue for OA treatment due to its capacity for specific gene silencing. siRNA molecules can modulate post-transcriptional gene expression, targeting key pathways involved in cellular proliferation, apoptosis, senescence, autophagy, biomolecule secretion, inflammation, and bone remodeling. This review delves into the mechanisms by which siRNA targets various cell populations within the OA milieu, offering a comprehensive overview of the potential therapeutic benefits and challenges in clinical application. By summarizing the current advancements in siRNA delivery systems and therapeutic targets, we provide a solid theoretical foundation for the future development of novel siRNA-based strategies for OA diagnosis and treatment, paving the way for innovative and more effective approaches to managing this debilitating disease.